AB0038 Tbk1: a key regulator and potential treatment target for interferon positive systemic lupus erythematosus and systemic sclerosis. (12th June 2018) - Huijser, E.; Bodewes, I.; van Helden-Meeuwsen, C.; Tas, L.; Huizinga, R.; Dalm, V.; van Hagen, M.; Groot, N.; Kamphuis, S.; van Daele, P.; Versnel, M.
Abstract : Background: Upregulation of type I interferons (IFN-I) is a hallmark of systemic autoimmune diseases like systemic lupus erythematosus (SLE) and systemic sclerosis (SSc). Three different receptor families are implicated in the induction of IFN-I production: Toll-like receptors (TLRs), RIG-like receptors (RLRs) and DNA-sensing receptors (DSRs). TANK-binding kinase (TBK1), is an important signalling hub downstream of RLRs and DSRs. TBK1 activates IRF3 and IRF7, leading to IFN-I production and subsequent induction of interferon-stimulated genes (ISGs). Objectives: To explore the potential of TBK1 inhibitors to downregulate IFN-I activation in SLE and SSc. Methods: TBK1, IRF3, IRF7 and STAT1 were determined by qPCR in PAXgene samples and phosphorylated-TBK1 (pTBK1) was analysed by flowcytometry in plasmacytoid dendritic cells (pDCs) from IFN-I positive (IFNpos) patients. Peripheral blood mononuclear cells (PBMCs) from SLE and SSc patients and TLR7-stimulated PBMCs from healthy controls (HCs) were cultured with the TBK1 inhibitors BX795 followed by analysis of ISGs. Results: Increased expression of TBK1, IRF3, IRF7 and STAT1 in whole blood and pTBK1 in pDCs was observed in IFNpos pSS, SLE and SSc patients compared to HCs. Upon treatment with BX795, PBMCs from IFNpos pSS, SLE, SSc and TLR7-stimulated HCs downregulated the expression of the ISGs MxA, IFI44, IFI44L, IFIT1 and IFIT3. The TBK1 inhibitor inhibited the secretion of IFN-I by TLR7-stimulated PBMCs from HCs. Conclusions: TBK1 inhibition reduced expression of ISGs in PBMCs from IFNpos SLE and SSc patients patients indicating TBK1 as a potential treatment target. Acknowledgements: The research for this manuscript was (partly) performed within the framework of the Erasmus Postgraduate School Molecular Medicine. The authors thank patients and healthy volunteers for taking part in this study. Disclosure of Interest: E. Huijser: None declared, I. Bodewes: None declared, C. van Helden-Meeuwsen: None declared, L. Tas: None declared, R. Huizinga: None declared, V. Dalm: None declared, M. van Hagen: None declared, N. Groot: None declared, S. Kamphuis: None declared, P. van Daele: None declared, M. Versnel Grant/research support from: Research funding Domainex